Towards an African Christian Theology of the Blood of Jesus Christ - Stephen Z. Yashim; Emmanuel Umar (E-Journal of Religious and Theological Studies, 2020)
This article proposes an African Christian theology of the blood of Jesus Christ which biblically explains and answers experiential questions raised in African historical and socio-cultural contexts. Through the process of conceptual analysis, articles on animal sacrifices in African Traditional Religions and articles in the theological fields of Biblical Theology and Systematic Theology are interrogated to propose an African Christian Theology of the blood of Jesus Christ. The proposed African Christian Theology of the blood of Jesus Christ posits that God acts on the basis of the vicarious shedding of the blood of Jesus Christ to incorporate believers into a Father-Child relationship that grants the believer access to a special divine benevolence. God’s benevolence is the means by which the believer experiences the transformative power of God that leads them to progressively experience improvements for their holistic well-being while anticipating the return of Jesus Christ to reinstate perfect holistic well-being for God’s people.